Expanding selves : an insider’s exploration of learner identity in second or other language learning - Fernandez, Irene (2018)
Identity is at the core of all human experience, and that is no different for teaching and learning experiences in second or other language learning classrooms. Yet the task of defining learner identity within these contexts has been subject to much debate, nested in the greater dichotomous landscape of linguistic and sociocultural schools of thought. Nonetheless, with the increasing trends in global migration and international students in higher education, there is an urgent need to define learner identity within these contexts to better support teaching and learning practices and experiences. Understanding learner identity also has further reaching implications for researchers, language and educational institutions, and the broader community in which these individuals reside outside of the language classroom.